Analysis of Factors Affecting Capital Structure and the Impact on LQ-45 Share Price in 2015-2018 - Arlan, Fikri; Salim, M Noor; Kurniasih, Augustina (International Journal of Business, Economics and Management, 2021)
This study aims to test and analyze the factors that affect the capital structure and its impact on the LQ-45 Share Price in 2015-2018. Research data is annual data for an observation period of 4 years (2015 to 2018). The sampling method used was purposive sampling. From a population of 45 companies, 31 companies meet the criteria to be sampled. The analysis method used in this research is regression panel data. The results showed that the Return on Assets, Return on Equity, Net Profit Margin together (simultaneously) have a significant effect on the Debt Equity Ratio and Return on Assets, Return on Equity, Net Profit Margin, and Debt Equity Ratio together ( simultaneous) has a significant effect on Share Prices. Partially, Return on Assets has a significant negative effect on Debt Equity, Return on Equity significantly positive effect on Debt Equity Ratio while Net Profit Margin has zero results on Debt Equity Ratio In Part, Return on Assets, Return on Equity and Net Profit Margin have no significant effect because of Share Prices and Debt Equity Ratio has a significant negative result on Share Prices.